ANALISIS PENGARUH STATUS PERKAWINAN DAN PENDIDIKAN TERHADAP PENDAPATAN TENAGA KERJA PEREMPUAN PADA INDUSTRI MANUFAKTUR - Lumbanraja, Tricia; Syafitri, Wildan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
This research aims to analyze the influence of marital status and educational level on female labor income in the manufacturing sector in East Java. The study also includes age, migration, and the number of dependents as control variables. The research method used is quantitative, utilizing data from the 2022 National Labor Force Survey (Sakernas). The analysis method employed in this study is multiple linear regression. The research findings indicate that education significantly and positively affects income. Marital status significantly and negatively influences income, while age significantly and negatively impacts income. Additionally, the number of dependents significantly and positively affects income. However, the variable of migration does not significantly influence income.